CSS for beginners - Kingston, Zachary; Safari eBooks ([S.I.] : LearnToProgram, 2013)
"Anyone who has worked in web development for more than five minutes can tell you: the difference between an outstanding site and a terrible site is the quality of the CSS. With our CSS course, you can learn to make high-quality, graphically amazing and thoroughly impressive web sites. All it takes is a little creativity and a strong understanding of CSS design and code and your website will look exactly the way you want it to. LearnToProgram's Zachary Kingston brings you this dynamic and comprehensive course. This CSS course is perfect for both beginners who don't understand how to use CSS and experts who don't understand why they cannot get their website to look exactly the way they want it to. Watch over 4 hours of engaging video lectures, sharpen your skills with fun and creative lab exercises, and study the dozens of style sheet examples provided. With this CSS course, you will become fully competent in CSS and master of your website!"--Resource description page.
Title from resource description page (viewed June 25, 2013).
Presenter, Zachary Kingston.
Keywords: Cascading style sheets; Web sites -- Design; Web site development; Electronic books